Placenta Accreta Spectrum: A Case Series of Five Patients - Ansari, Sana; Ansari, Meraj Alam; Mushtaq, Rehana; Shah, Ravi Kumar; Shah, Pravin; Shrestha, Ruby; Prasad, Jagat Deep; Khatun, Tarannum (Med Phoenix, 2024)
Introduction: In the present world as the incidence of Caesarean section have increased, Placenta accreta also has increased and considered as an important cause of maternal and fetal/neonatal morbidity and mortality. In the present case series, we report a case series of five patients of placenta accreta spectrum diagnosed intraoperative presenting obstetric emergency. The American College of Obstetricians and Gynecology generally recommends for Caesarean Section Hysterectomy in cases of placenta accreta because removal of placenta is associated with significant hemorrhage. We present the case series of five patients as only few studies described Caesarean Hysterectomy in patients with placenta accreta spectrum with images as well as to highlight the surgical difficulties and need for further research into the prevention of abnormal placental development and to prevent their risk of massive hemorrhage.